2023
DOI: 10.3390/agronomy13020280
|View full text |Cite
|
Sign up to set email alerts
|

Interactions and Regulatory Functions of Phenolics in Soil-Plant-Climate Nexus

Abstract: Phenols are major compounds produced by plant species as a peripheral stimulus or as a regulatory defense mechanism under different environmental biotic stresses. These secondary metabolites are generated from shikimic and acetic acid metabolic pathways. The aromatic benzene ring compound plays an important role in plant development, especially in the defense forefront. They provide structural integrity and support to the plants. Phenolic phytoalexins released by pathogen/arthropod-attacked or wounded plants n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 134 publications
0
16
0
Order By: Relevance
“…Secondary metabolites serve critical roles in plants, including adaptation to the environment, defense mechanisms, metal transport, and symbiotic relationships, acting as hormones, and promoting cellular differentiation. 26,27 Phenolic compounds, with hydroxyl groups on aromatic rings, are crucial secondary metabolites, categorized into four main types as flavonoids, phenolic acids, stilbenes, and lignans. 28,29 Resorcinol, a phenolic chemical (1,3-isomer of benzenediol) with the formula C 6 H 4 (OH) 2 , was utilized in this investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary metabolites serve critical roles in plants, including adaptation to the environment, defense mechanisms, metal transport, and symbiotic relationships, acting as hormones, and promoting cellular differentiation. 26,27 Phenolic compounds, with hydroxyl groups on aromatic rings, are crucial secondary metabolites, categorized into four main types as flavonoids, phenolic acids, stilbenes, and lignans. 28,29 Resorcinol, a phenolic chemical (1,3-isomer of benzenediol) with the formula C 6 H 4 (OH) 2 , was utilized in this investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Key physiological pathways crucial for plant growth, reproduction, and metabolism, including glycolysis, Krebs cycle, and Calvin cycle, are regulated by primary plant metabolites like carbohydrates, amino acids, organic acids, and enzymes. , Conversely, secondary metabolites, including phenols, alkaloids, flavonoids, and terpenoids, assume a substantial role in the plant’s stress response and defense mechanisms , and are not directly associated with plant growth. Primary metabolites are essential for plant metabolism and are vital for the production of secondary metabolites. , While the absence of primary metabolites may not severely affect plant survival, their presence is crucial for synthesizing secondary metabolites. Secondary metabolites serve critical roles in plants, including adaptation to the environment, defense mechanisms, metal transport, and symbiotic relationships, acting as hormones, and promoting cellular differentiation. , Phenolic compounds, with hydroxyl groups on aromatic rings, are crucial secondary metabolites, categorized into four main types as flavonoids, phenolic acids, stilbenes, and lignans. , …”
Section: Introductionmentioning
confidence: 99%
“…For the TA and HT categories, the impact of phenol has been attributed to its toxicity even at low concentrations. Some studies have shown that small concentrations in water sources or wastewater inhibit soil bacterial metabolism and plant cellular functioning when using phenol‐contaminated irrigation 58 . In contrast, furfural production did not show impacts higher than 3% for all indicators.…”
Section: Resultsmentioning
confidence: 85%
“…Moreover, Ligularia virgaurea has been shown to release large amounts of volatile allelopathic compounds (Wu et al, 2011;Zhang et al, 2011;Arjmand et al, 2013) and to influence soil fungal community composition (Shi et al, 2011) and host-specific fungal endophytes (Aschehoug et al, 2014). Monoterpenoids are the main allelopathic substances produced by L. virgaurea, accounting for 16.6% of the total volatiles, with other allelopathic compounds including phenolic, terpenoid, alkane and aromatic compounds (Ma et al, 2005), which can also affect soil organisms (Misra et al, 2023). While both L. virgaurea roots and leaves produce allelopathic compounds, and leaf-derived allelopathic substances may enter soil through rainwater leaching, the allelopathic effect of roots has been shown to be stronger than that of leaves (Ma et al, 2006;Wu et al, 2011).…”
Section: The Effects Of Ligularia Virguarea On Understory Plants and ...mentioning
confidence: 99%